Genome‐wide mutation analysis in precancerous lesions of endometrial carcinoma. Issue 1 (13th November 2020) - Li, Lihong; Yue, Pinli; Song, Qianqian; Yen, Ting‐Tai; Asaka, Shiho; Wang, Tian‐Li; Beavis, Anna L; Fader, Amanda N; Jiao, Yuchen; Yuan, Guangwen; Shih, Ie‐Ming; Song, Yan
Abstract: Clinicopathological evidence supports endometrial atypical hyperplasia (AH) or endometrial intraepithelial neoplasia as the precursor of uterine endometrioid carcinoma (EC), the most common gynecologic malignancy. However, the pathogenic progression from AH to EC remains unclear. Here, we employed whole‐exome sequencing to identify somatic mutations and copy number changes in micro‐dissected lesions from 30 pairs of newly diagnosed AH and EC. We found that all but one pair of AHs shared the same DNA mismatch repair status as their corresponding ECs. The percentage of common mutations between AH lesions and corresponding ECs varied significantly, ranging from 0.1% to 82%. Microsatellite stable AHs had fewer cancer driver mutations than ECs (5 versus 7, p = 0.017), but among microsatellite unstable AHs and ECs there was no difference in mutational numbers (36 versus 38, p = 0.65). As compared to AH specimens, 19 (79%) of 24 microsatellite stable EC tumors gained new cancer driver mutations, most of which involved PTEN, ARID1A, PIK3CA, CTNNB1, or CHD4 . Our results suggest that some AH lesions are the immediate precursor of ECs, and progression depends on acquisition of additional cancer driver mutations. However, a complex clonal relationship between AH and EC can also be appreciated, as in some cases both lesions diverge very early or arise independently, thus co‐developing with distinct genetic trajectories. Our genome‐wide profile of mutations in AH and EC shines new light on the molecular landscape of tumor progression. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.